A phase I/II feasibility vaccine study by autologous leukemic apoptotic corpse-pulsed dendritic cells for elderly AML patients. Issue 10 (3rd October 2021) - Chevallier, Patrice; Saiagh, Soraya; Dehame, Virginie; Guillaume, Thierry; Peterlin, Pierre; Bercegeay, Sylvain; Le Bris, Yannick; Bossard, Céline; Gauvrit, Isabelle; Dreno, Brigitte; Juge-Morineau, Nadine; Béné, Marie C.; et al.
ABSTRACT: This was a phase I/II study testing the feasibility of a vaccine by autologous leukemic apoptotic corpse-pulsed dendritic cells (DC) in elderly acute myeloid leukemia (AML) patients in first or second complete remission. Pulsed DC were administered at doses of 9 × 10 6 subcutaneously (1 mL) and 1 × 10 6 intra-dermally (0.1 mL). Five doses of vaccine were planned on days +1 + 7 + 14 + 21 and +35. Five DC-vaccines were produced and injected for all five patients included in the study. No severe adverse event was documented. Larger Phase 2 studies are now required to precise the role of DC-vaccines with leukemic apoptotic bodies in older as well as younger AML populations. (Clinicaltrials.gov NCT01146262)